Fuelwood Production and Utilization Pattern along an Altitudinal Gradient in Kosi Watershed of Kumaun Himalaya - Kanwal, Manmohan Singh; Yadava, Anil Kumar; Vishvakarma, S. C. R. (Indian Forester, 2023)
Wood is a primary source of energy for billions of people, particularly in Himalayan region. With rapid increase in population, per capita consumption of fuelwood has increased, which resulted into the over exploitation and threat to woody species of this region. Present study deals with fuelwood production and consumption pattern in three villages of Kosi watershed area situated at different altitudinal zones in Kumaun Himalaya. Study revealed that total fuel wood production was in the range of 25.09 & 49.21 MT at study sites. Major source of fuel wood production was natural forests, which share about 76.91 to 82.5% of the total annual fuel wood production while agroforestry systems contribute about 10.56 to 7.53% of the total annual fuel wood production. Quercus leucotrichophora, Celtis australis, Toona ciliata, Bombax ceiba, Boehmeria rugulosa and Bauhinia variegata were important fuel wood tree species of Agroforestry system. Per capita average fuelwood consumption at three altitudinal zones was in between 3.11 kg to 1.00 kg capita-1 day-1 with maximum consumption at highest altitude during winters and least consumption at lowest altitude during summer season. The present study would be helpful in planning and designing suitable technologies to develop energy plantations in the Kumaun region.